Reconstructing the Islamic Green Economy: Ethics, Institutions, and Sustainable Development - Syahrizul (Journal of Islamic Economic Studies, 2026)
This study reconstructs the Islamic Green Economy as an integrative paradigm that connects ethical foundations, institutional dynamics, and sustainable development pathways. The research responds to the limitations of mainstream green economy approaches that tend to emphasize technocratic solutions while marginalizing moral and spiritual dimensions of economic behavior. Using a qualitative descriptive–analytical method, the study critically examines classical and contemporary Islamic economic literature, policy documents, and empirical studies on sustainable Islamic finance. The analysis is conducted through three stages: normative analysis based on maqāṣid al-sharīʿah, institutional analysis of Islamic financial and social institutions, and interpretative synthesis. The findings indicate that sustainability in Islamic economics is intrinsically embedded in its ethical framework, particularly through principles of stewardship (khilāfah), balance (mīzān), justice, and the prohibition of excess (isrāf). Institutionally, the Islamic Green Economy is manifested through innovations such as green sukuk, environmentally oriented waqf, Islamic microfinance, and blended social finance models. These developments signify a shift from formal Shariah compliance toward value-driven and impact-oriented economic practices. The study concludes that the Islamic Green Economy offers a holistic and ethically grounded development paradigm that aligns environmental sustainability with social justice and long-term human well-being, contributing an alternative framework for sustainable development, particularly in Muslim-majority and developing countries.